Repositioning sovereignty? Sovereign encounters with organized crime and money laundering in the realm of accountants. (November 2014) - Hörnqvist, Magnus
This article repositions sovereignty on the basis of a study of recent regulatory approaches to organized crime and money laundering. The spread of techniques across administrative domains is traced through organizational documents and interviews with practitioners, and related to an observed trend toward integration between policing research and regulation research. The same trend, however, assigns sovereignty to the periphery. A richer notion of sovereignty is recovered through a reading of the classical theorists, and used to tease out the articulation of sovereignty in current state strategies. Theorizing 'sovereignty at the center' as opposed to 'sovereignty at the periphery' challenges basic assumptions about the relationship between the state and economic activity, and in particular about the utility-oriented character of state violence.